Pengaruh Iklim Komunikasi Organisasi Dan Gaya Komunikasi Walikota Surabaya Periode 2021 – 2024 terhadap Kinerja Kader Surabaya Hebat - Aditya Luhur Pambudi; Tony S Soekrani; M Reza Ishadi Fadillah; Didik Sugeng Widiarto (Journal Communication Specialist, 2023)
ABSTRACTKader Surabaya Hebat (KSH) is one of the instruments that should be used as best as possible by the mayor of surabaya period 2021 2024 with the climate of organization communication and communication style. The city's government program of Surabaya can run from top to bottom well when there is synergy in the form of service to the people of the city of Surabaya. Kaders dominated by the housewifes were able to have a profound impact on running the wheels of government related to early detection problems that the city authorities were unable to reach Based on the result analysis correlation can be inferred that the climate communication organization and communication style has a very strong impact and in line with the performance Kader Surabaya Hebat. From the results of the regression analysis can be concluded that variations (up or down) of the frame performance can be explained by the variable of the organization's communication climate and the variable of the communication style. At the same time other variables affected the rest outside the specified. T that testing shows on this fact, variable - variable climate communication organization and communication style significantly affect performance variables cadres. Based on f test simultaneously or jo the same variable of the organization's communication climate and the variable of communication styles have an influence on the variable of frame performance